2019
DOI: 10.1186/s40168-019-0679-5
|View full text |Cite
|
Sign up to set email alerts
|

Chemotherapy-induced oral mucositis is associated with detrimental bacterial dysbiosis

Abstract: Background Gastrointestinal mucosal injury (mucositis), commonly affecting the oral cavity, is a clinically significant yet incompletely understood complication of cancer chemotherapy. Although antineoplastic cytotoxicity constitutes the primary injury trigger, the interaction of oral microbial commensals with mucosal tissues could modify the response. It is not clear, however, whether chemotherapy and its associated treatments affect oral microbial communities disrupting the homeostatic balance b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

4
167
1
6

Year Published

2020
2020
2023
2023

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 186 publications
(198 citation statements)
references
References 64 publications
4
167
1
6
Order By: Relevance
“…Interestingly, strong correlation was observed in salivary levels of Lactobacillus species and fluctuations of saliva flow rates and salivary pH levels during radiotherapy [80]. Another report demonstrated that chemotherapyinduced oral mucositis was associated with a decrease in salivary levels of health-associated bacterial genera, including Streptococcus, Actinomyces and Veillonella in combination with an increase of the periodontitis-associated genera Fusobacterium and Prevotella, and increased transcription of genes related to innate immunity and apoptosis in oral epithelial cells from patients with oral mucositis [81].…”
Section: Cancermentioning
confidence: 97%
“…Interestingly, strong correlation was observed in salivary levels of Lactobacillus species and fluctuations of saliva flow rates and salivary pH levels during radiotherapy [80]. Another report demonstrated that chemotherapyinduced oral mucositis was associated with a decrease in salivary levels of health-associated bacterial genera, including Streptococcus, Actinomyces and Veillonella in combination with an increase of the periodontitis-associated genera Fusobacterium and Prevotella, and increased transcription of genes related to innate immunity and apoptosis in oral epithelial cells from patients with oral mucositis [81].…”
Section: Cancermentioning
confidence: 97%
“…It has been previously shown that cytotoxic and cisplatin compounds have direct anti-Candida activity and also inhibit filamentation/conidation (12). More recently, investigators demonstrated that the oral microbiome is disrupted by 5-fluorouracil (5-FU) and doxorubicin chemotherapy, but they did not observe major changes in the composition of the mycobiome (13). Moreover, mice receiving both 5-fluorouracil and C. albicans had a loss of bacterial diversity and showed endogenous overgrowth of organisms such as Enterococcus and Stenotrophomonas in the oral mucosa (14).…”
mentioning
confidence: 99%
“…To our knowledge, the changes in the oral mycobiome occurring as a result of chemotherapy have been studied only in regard to their role in chemotherapy-induced mucositis in the setting of 5-fluorouracil (5-FU) or doxorubicin-based chemotherapy in mice and humans (13,14). In patients, although the authors expected chemotherapy to affect the oral mycobiome, no major changes in the composition of fungal communities were observed (13). Thus, our study would be the first to show specific changes in the oral mycobiome associated with chemotherapeutic intensity and type.…”
mentioning
confidence: 99%
“…Chemotherapeutic agents may affect gut microbial communities by disrupting the homeostatic balance among resident microorganisms; meanwhile, they can accelerate the microbe evolution at molecular level [4][5][6]. Many recent studies have explored the interaction between microbiota and anticancer drugs along with interventions aimed at shaping microbiota to optimize drug efficacy and reduce side effects [7].…”
Section: Introductionmentioning
confidence: 99%